FAKTOR SITUASIONAL DALAM PELATIHAN TEKNOLOGI KONTRASEPSI TERKINI /CTU (CONTRACEPTIVE TECHNIQUE UPDATE) BAGI BIDAN - Intan Gumilang; Baiq Yuni Fitri Hamidiyanti; Ristrini Ristrini; Gurendro Putro; Adang Bachtiar (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2021)
Intra Uterine Device users continued to decline from the 2012 IDHS as much as 4.9%, in the 2017 IDHS data as much as 3.9%. This is one of the factors to improve the quality of health workers in training for family planning services. Improving the quality of midwifery services is carried out with various kinds of training. One of them is the CTU (Contraceptive Update) program for midwives. Effective training is influenced by a variety of situational factors. Situational factors must be identified to achieve the training objectives. The purpose of this study was to analyze the factors that influence the effectiveness of IUD training for midwives. Descriptive research method with a questionnaire instrument includes the factors of participants, trainers, facilities and infrastructure as well as training materials. The research design used was descriptive with analysis of results using the Rasch model. Situational factors in a training affect the effectiveness of the training. These factors are the participant factor, the trainer factor, the advice and infrastructure factor, and the training material factor. Suggestions in the future for training to pay more attention to these factors in order to achieve an effective training activity